Switching to Tumescent Dissection in Mastectomy - Emna Bakillah; Ari D. Brooks; Seye Adekeye (The Breast Journal)
Conclusion: TUM yields comparable results with decreased overall complication rates compared to electrocautery dissection. Electrocautery thermal effect may account for skin-related complications. Additionally, tumescent mastectomies have shorter length of operative time which could reduce the risk of complications associated with increased time under general anesthesia.